Walkshop ‘Nuclear risks and long-term peacekeeping’: 26.06.2025 – 01.07.2025 - IGJR-Editors (Intergenerational Justice Review)
Since 2021, the FRFG has organised Walkshops on the topics social security and intergenerational contracts, atomic waste, the coal phase-out, and climate change. In 2025, the Walkshop will focus on the topic ‘Nuclear risks and long-term peacekeeping’.